Proposals for a harmonised system of incentives for industry, tourism and services for CARICOM - McIntyre, Arnold ([s.n.] [S.l], 1993)
Presents three studies on proposals for harmonised incentives to industry, tourism and services. Analyses the important conceptual issues that should be addressed. Reviews the original and proposed revisions to the harmonised scheme of incentives, as well as existing tourism incentives. Provides a broad framework for harmonised incentives to tourism. Examines the services sector in CARICOM, analyses the salient policy issues involved in promoting export services and proposes an initial set of fiscal incentives for the development of export services.